Influences of Mg-Cr filler materials in Friction Stir Process of Aluminium-based dissimilar alloys. (2022) - Haribalaji, V.; Boopathi, Sampath; Mohammed Asif, M.; Yuvaraj, T.; Velmurugan, D.; Anton Savio Lewise, K.; Sudhagar, S.; Suresh, P.
Abstract: In this research, the AA2014 and AA5052 have been welded by Friction stir process (FSP) with various percentages of filler material. Al-Cu (AA2014) and Al-Mg (AA5052) Alloys have been selected as base materials and various percentages of weight ratios of Magnesium (Mg) and Chromium (Cr) were used as filler substances to examine the impacts on tensile strength and corrosion rate. The tool rotational speed, depth of plunge depth, welding speed, and powder mixing ratio have been considered as controlling parameters and the one-variable-at-a-time (OVAT) approach has been applied to the design and analysis. The effects of each factor on the tensile and corrosion rate have been analyzed. While increasing Mg element, powder mixing ratio, the welding quality, tensile strength, and corrosion factors were improved.